Rosyjskie złożenia: aspekt historyczny - Николаев, Геннадий; Николаева, Наталия (Studia Rossica Posnaniensia, 2018)
Compound words are known in the Russian language since the first written texts of different genre and stylistic characteristics. The formation of composites was carried out in two productive ways: by the non-morphological semantic method of fusion and by morphological addition. Within both methods (in literary texts) the calques of Greek composites and the development of East Slavic word formations in their sample are also noted. Both methods were interrelated, and an interaction of derivatives occurred in their sphere.